2003
DOI: 10.1029/2002jd003326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seasonal and spatial variations of albedos from Moderate‐Resolution Imaging Spectroradiometer (MODIS) and Common Land Model

Abstract: [1] This paper compares seasonal and spatial variations of Moderate Resolution Imaging Spectroradiometer (MODIS) albedos with those from the Common Land Model (CLM) by land cover type. MODIS albedo data in the year 2001 were used to determine seasonal, spatial, and land cover dependence at 1 km resolution and to investigate the biases in CLM. Albedo dependence on vegetation type is smaller than that on snow and soil. Snow causes the largest temporal and spatial variations, especially in the visible band (0.3-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 35 publications
6
107
1
1
Order By: Relevance
“…In general, the snow cover is vertically inhomogeneous, and sometimes it is optically thin (Voisin et al, 2012). The stratified structure of snow cover will lead to the discrepancies between computed spectral albedo from semi-infinite snow cover and measured albedo (Aoki et al, 2000;Grenfell, 1994;Kuipers Munneke et al, 2008;Zhou et al, 2003). In this study, we usually collected snow samples from the top 5-10 cm.…”
Section: Reflectance Measurements and Albedo Simulationsmentioning
confidence: 99%
“…In general, the snow cover is vertically inhomogeneous, and sometimes it is optically thin (Voisin et al, 2012). The stratified structure of snow cover will lead to the discrepancies between computed spectral albedo from semi-infinite snow cover and measured albedo (Aoki et al, 2000;Grenfell, 1994;Kuipers Munneke et al, 2008;Zhou et al, 2003). In this study, we usually collected snow samples from the top 5-10 cm.…”
Section: Reflectance Measurements and Albedo Simulationsmentioning
confidence: 99%
“…This has allowed for the careful evaluation of albedo in various LSMs (e.g. Wei et al, 2001;Oleson et al, 2003;Zhou et al, 2003;Wang et al, 2004) and the development of vegetation and soil albedo parameterisations (e.g. Liang et al, 2005;Yang et al, 2008).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Several studies have addressed the deficiencies in the parameterisation of land surface albedo in the Community Land Model 2.0 by comparing the model-computed albedo against MODIS observations (Oleson et al, 2003;Zhou et al, 2003;Wang et al, 2004). These studies report better agreement of simulated albedo to observations during summer (Oleson et al, 2003), overestimation of simulated albedo over snow-covered regions by as much as 20% and underestimation of the albedo in the desert regions of the Sahara and the Arabian Peninsula (Oleson et al, 2003;Zhou et al, 2003).…”
Section: The Clm-modis Experimentsmentioning
confidence: 94%
“…These studies report better agreement of simulated albedo to observations during summer (Oleson et al, 2003), overestimation of simulated albedo over snow-covered regions by as much as 20% and underestimation of the albedo in the desert regions of the Sahara and the Arabian Peninsula (Oleson et al, 2003;Zhou et al, 2003). These studies suggested CLM needs to be improved to have a better representation of albedo, leaf area index (LAI), snow cover etc.…”
Section: The Clm-modis Experimentsmentioning
confidence: 98%